ANALYSIS OF HARMONY IN MOVEMENT AND SOUND: SPIRITUAL MEANING LET ALL PRAISE GOD - Levinson Y A Simaela; Junita Batubara; Dewi Tika Lestari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study discusses a comprehensive analysis of the choral work "Let Everything That Breathes Praise the Lord" created by Levinson Simaela, focusing on its musical structure, harmony, and performative potential.This song was inspired by Psalm 150 and became a mandatory song at the Church Choir Festival (PESPARAWI) of SMGT (Toraja Church Sunday School) throughout the East Makassar Classis in 2022.This work is a silent witness to the victory of the SMGT Satria Kasih Makassar Children's Choir at the event. Researcheras the creator of this work, I intend to identify the compositional elements in the score, explore the performance implications of the existing notation, and examine the inclusion of Torajan nuances through the use of local language lyrics and Torajan drum accompaniment.The use of Torajan lyrics and specific directions for traditional instruments such as the Torajan drum demonstrate an effort to integrate local cultural richness into church music.Using qualitative descriptive methods of formal music analysis supported by ethnographic review, this study examines how the components of melody, rhythm, and harmony interact to shape the overall work. In addition, this article discusses how the tempo direction, dynamics, and "(Sambil Menari)" instructions in the score can influence interpretation and presentation on stage. The incorporation of Torajan lyrics and the option of Torajan drum accompaniment are important points in understanding how this work inculturates regional cultural values ​​into expressions of church praise. The findings of this study are expected to provide a deeper understanding of adaptive choral composition practices, as well as the contribution of music to enriching spiritual culture in Indonesia.